Rapid Review: i -Voting Election General 2024 in Indonesia - Daniel Gilrandy Tirasbudi; Irwansyah Irwansyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Industry 4.0 has advanced technology in contributing more to human life. These advances have an impact on every aspect of human life, especially information and communication technology. Uses and Gratifications Theory (UGT) is the basis for increasing the number of participants in the General Election system that meets the needs of voters. This research was conducted using a rapid review to produce policy recommendations to the government quickly within a limited time. The method used in a coherent study is PRISMA, to find the media choices that are most widely used by Indonesians and to find opportunities including the threat of simultaneous general elections in Indonesia in 2024. The findings show the many advantages of the voting system because of the greater benefits compared to the conventional system.  especially i -voting has become an efficient system compared to the previous General Election System. The main threat of the i -voting system lies in network security; this condition already exists namely blockchain solutions. Changes in the General Election System cannot be interrupted because of technology, currently, changes in the General Election system are still running in place due to political interests. The relevant system development to be implemented is the combination of i -voting with e-voting, this system can provide solutions for voters who have resource constraints with e-voting and time constraints with i - voting.